The Creative Thinking Process of Students with Adversity Quotient Personality and Metacognition Level in Solving Open-Ended Problems Reviewed from the Information Processing Theory - Rusdyi Habsyi; Asmira Sudiman; Muhammad Ikram; Rusmin R.M. Saleh; Ageng Triyono; Karman La Nani (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The issue of creative thinking encompasses various contexts, including those about Adversity Quotient students, necessitating further elucidation of the problem to ascertain students' metacognitive levels. This research constitutes a qualitative descriptive exploratory study aimed at delineating the creative thinking process of students, with a focus on students' Adversity Quotient and metacognition levels, as examined through the lens of information processing theories. The study participants were 29 students from the 11th grade of SMA. The research methodology involved administering tests to students, with subsequent analysis of the results utilizing the exploratory descriptive method, wherein the researcher categorized students based on their Adversity Quotient and metacognition levels. Data collection in this study employed instruments in the form of open-ended questions and interview guidelines. Initial test results revealed that seven students could provide comprehensive answers to the questions, nine offered partial responses, and 13 did not respond. Further analysis of the test results indicated that one subject classified as the